Strategies for the implementation of a nasal decolonization intervention to prevent surgical site infections within the Veterans Health Administration - Hockett Sherlock, Stacey; Goedken, Cassie Cunningham; Balkenende, Erin C.; Dukes, Kimberly C.; Perencevich, Eli N.; Reisinger, Heather Schacht; Forrest, Graeme N.; Pfeiffer, Christopher D.; West, Katelyn A.; Schweizer, Marin (Frontiers in Health Services, 2022)
As part of a multicenter evidence-based intervention for surgical site infection prevention, a qualitative study was conducted with infection control teams and surgical staff members at three Department of Veterans Affairs Healthcare Systems in the USA. This study aimed to identify strategies used by nurses and other facility champions for the implementation of a nasal decolonization intervention. Site visit observations and field notes provided contextual information. Interview data were analyzed with inductive and deductive content analysis. Interview data was mapped to the Expert Recommendations for Implementing Change (ERIC) compilation of implementation strategies. These strategies were then considered in the context of power and relationships as factors that influence implementation. We found that implementation of this evidence-based surgical site infection prevention intervention was successful when nurse champions drove the day-to-day implementation. Nurse champions sustained implementation strategies through all phases of implementation. Findings also suggest that nurse champions leveraged the influence of their role as champion along with their understanding of social networks and relationships to help achieve implementation success. Nurse champions consciously used multiple overlapping and iterative implementation strategies, adapting and tailoring strategies to stakeholders and settings. Commonly used implementation categories included: “train and educate stakeholders,” “use evaluative and iterative strategies,” “adapt and tailor to context,” and “develop stakeholder interrelationships.” Future research should examine the social networks for evidence-based interventions by asking specifically about relationships and power dynamics within healthcare organizations. Implementation of evidence-based interventions should consider if the tasks expected of a nurse champion fit the level of influence or power held by the champion. Trial registration ClinicalTrials.gov, identifier: NCT02216227.